Incorporating Character Values in English Class through Mini-drama Performance - Wiyaka Wiyaka; Siti Lestari; Dias Andris Susanto (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
This paper presents the result of a small-scale research which was aimed to find out a model of incorporating character values in English classroom of elementary schools. The government is now campaigning character education that should be incorporated in all subjects through direct and indirect teaching. For subjects such as English, character values need not be taught directly in class, but they are infused during the prosess of teaching and learning.  The question arose among the teachers is how to incorporate character values in the subjects of which content is not particularly set to teaching moral values. The proposed model in this study is by using mini drama performance. The research took place at 4 elementary schools (ES) in Semarang municipality, consisting of 3 public schools and 1 private school. The data were collected from observation and interview with the teachers. The field notes and the results of interview were analyzed descriptively to to portray the existing model of teaching English in general, and teaching character values in particular.